2020
DOI: 10.1186/s12891-020-03654-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison between single-row with triple-loaded suture anchor and suture-bridge double-row rotator cuff repair

Abstract: Background Numerous biomechanical and clinical studies comparing different techniques for rotator cuff repair have been reported, yet universal consensus regarding the superior technique has not achieved. A medially-based single-row with triple-loaded suture anchor (also referred to as the Southern California Orthopedic Institute [SCOI] row) and a suture-bridge double-row (SB-DR) with Push-Locks have been shown to result in comparable improvement in treating rotator cuff tear, yet the biomechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A more recent biomechanical study of six fresh-frozen cadaveric shoulders compared single-row with triple-loaded suture anchors with suture-bridge double-row repairs for full thickness supraspinatus tears. Superior biomechanical properties were found in the single-row group, with this group exhibiting higher ultimate failure loads (326 N vs 300 N) [23] . A recently published review reported a progression rate of 40% in conservatively treated full-thickness tears after 4 years' observation [24] .…”
Section: Discussionmentioning
confidence: 85%
“…A more recent biomechanical study of six fresh-frozen cadaveric shoulders compared single-row with triple-loaded suture anchors with suture-bridge double-row repairs for full thickness supraspinatus tears. Superior biomechanical properties were found in the single-row group, with this group exhibiting higher ultimate failure loads (326 N vs 300 N) [23] . A recently published review reported a progression rate of 40% in conservatively treated full-thickness tears after 4 years' observation [24] .…”
Section: Discussionmentioning
confidence: 85%
“…The goals of rotator cuff repair are to reduce pain and to restore shoulder function, which require anatomic footprint restoration with minimum gap formation, broad tendon-to-bone contact area, and biological stimulation to promote tendonebone healing. [1][2][3][4] Theoretically, the standard suture bridge has many advantages over single-and double-row repair. [5][6][7] Clinically, the rotator cuff cannot be adequately mobilized and anatomic bone-to-tendon repair would be difficult because of excessive tension.…”
Section: Discussionmentioning
confidence: 99%
“…Suture-bridge repair was introduced by using 2 rows of anchors to improve tendon-to-bone contact over the footprint, together with decreased motion on the boneetendon interface and increased resistance to rotational forces. [1][2][3][4] Although this technique leads to several advantages over the standard single-row or doublerow repair, the incidence of retear cannot be avoided. [4][5][6][7] The most possible explanations may include greater tension for the repaired tendon than expected; tendon strangulation caused by medial row knottying; and further damage to the degenerated torn tendon.…”
mentioning
confidence: 99%
“…Another study conducted by Mazzocca et al [ 31 ] confirmed that the single-row repair technique was similar to the double-row techniques in load-to-failure, cyclic displacement, and gap formation, which was attributed to a larger number of suture passes through the tendon. He et al [ 33 ] reported that rotator cuff repair using the SCOI row method has superior biomechanical properties when compared with the double-row method. Indeed, our results support this view.…”
Section: Discussionmentioning
confidence: 99%